Visual evoked potentials to change in coloration of a moving bar - Murd, Carolina; Kreegipuu, Kairi; Kuldkepp, Nele; Raidvee, Aire; Tamm, Maria; Allik, Jüri (Frontiers in Human Neuroscience, 2014)
In our previous study we found that it takes less time to detect colour change in a moving object compared to colour change in a stationary one (Kreegipuu et al., 2006, Vision Research 46(11), 1848-1855). Here, we replicated the experiment, but in addition to reaction times we measured visual evoked potentials, to see whether this effect of motion is revealed at the cortical level of information processing. We asked our subjects to detect colour changes in stationary (0º/s) and moving bars (4.4 and 17.6º/s). Psychophysical results replicate the findings from the previous study showing decreased reaction times to colour changes with increase of velocity of the colour changing stimulus. The effect of velocity on visual evoked potentials was opposite to the one found on reaction times. Except for component N1, the amplitudes of visual evoked potentials elicited by the colour change of faster moving objects were reduced than those elicited by the colour change of slower moving or stationary objects. The only significant effect of velocity on latency of peaks was found for P2 in frontal region. The results are discussed in the light of change-to-change interval and the two methods reflecting different processing mechanisms.